2021
DOI: 10.1016/j.xjtc.2021.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Acute type A aortic dissection and the consequences of a patent false lumen

Abstract: Acute type A aortic dissection (ATAAD) is a lifethreatening condition associated with high mortality and morbidity. 1 Without immediate surgical repair, mortality rates approach 50% within the first 48 hours. [2][3][4][5] Despite improvements in surgical technique and critical care, the short-and long-term mortality and morbidity associated with ATAAD, particularly the DeBakey I subgroup, remains high. Although standard repair for ATAAD involves resection of the primary intimal tear in the proximal aorta, pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…The less aggressive partial arch replacement with shorter circulatory arrest times and periprocedural complications has just been associated with a higher rate of residual dissections and new entries at the distal anastomotic site in a meta-analysis. 69 Thus, a current expert consensus comes to the recommendation that arch replacement potentially including elephant trunks may be an option in experienced hands. [68][69][70][71] In the treatment of terminal heart failure, the continuing shortness of donor organs makes left ventricular assist device therapy more and more a long-term alternative to heart transplantation.…”
Section: Tricuspid Valvementioning
confidence: 99%
See 3 more Smart Citations
“…The less aggressive partial arch replacement with shorter circulatory arrest times and periprocedural complications has just been associated with a higher rate of residual dissections and new entries at the distal anastomotic site in a meta-analysis. 69 Thus, a current expert consensus comes to the recommendation that arch replacement potentially including elephant trunks may be an option in experienced hands. [68][69][70][71] In the treatment of terminal heart failure, the continuing shortness of donor organs makes left ventricular assist device therapy more and more a long-term alternative to heart transplantation.…”
Section: Tricuspid Valvementioning
confidence: 99%
“…69 Thus, a current expert consensus comes to the recommendation that arch replacement potentially including elephant trunks may be an option in experienced hands. [68][69][70][71] In the treatment of terminal heart failure, the continuing shortness of donor organs makes left ventricular assist device therapy more and more a long-term alternative to heart transplantation. A meta-analysis demonstrated that left ventricular assist device therapy is able to provide similar 2-year survival compared with heart transplantation.…”
Section: Tricuspid Valvementioning
confidence: 99%
See 2 more Smart Citations
“…Effectively closing off the false lumen (FL) flow can lead to improved late remodeling. (9,10) Adverse remodeling, which has been linked to a nearly 20% risk of increased mortality at five years, can be caused by distal new entry tears. (11)(12)(13) Performing extended arch repair (EAR) in TAAAD is increasingly popular due to their ability to promote late remodeling and reduce the risk of distal new entry tears.…”
Section: Introductionmentioning
confidence: 99%